Effect of fungus Meripilus giganteus (Pers.) P. Karst. on occurrence and development of false heartwood and rot in Fagus sylvatica L. round wood - Arač, Krunoslav (Array, 2021)
Common beech is one of the most widespread and important European tree species, widely used in timber industry and for energy production. Under specific set of complex factors, it facutatetivly develops false heartwood, which considerably decreases market demand and value of processed logs. Due to its properties, false heartwood is more susceptible to attack of wood decay fungi, which leads to further loss of wood quality and value. One of the most common fungi able to cause heart rot in beech is Meripilus giganteus, known for its spread in the basal parts of the tree, where it can affect most valuable sections of round wood. The aims of this study were to monitor the distribution of fungus and appearance of its fruiting bodies in research area, and to analyze the extent of fungus impact on shape and size of false heartwood and occurrence and length of rot in infected trees, while taking into account the observed stem damage as a possible influential factor. Fruiting bodies occurrence, life span and position on a tree were monitored during a six-year period. For trees with confirmed infection, stem damage was evaluated and appointed to one of four size classes. False heartwood shape and share in associated stem cross-section were observed and measured on 1–4 cross-sections per tree at different heights, and compared between infected and uninfected trees. If present, length of wood decay extent on butt-log was measured. The obtained results confirmed increased susceptibility of mature trees to infection, which seemed to occur mostly via roots from where mycelium spread into stem base. It was found that Meripilus giganteus has a significant impact on enlargement and change of FH shape from cloud- to star-like, up to approximately 5 m of the stem height, thus causing devaluation of the first assortments.